Association of patent ductus arteriosus (PDA) with prematurity and low birth weight neonates - Wani, Gh Rasool; Parray, Nazir Ahmad; Lone, Mohd Rafiq; Ganie, Nisar Ahmad; Hussain, Anwar; Islam, Junaid Ul; Mohammad, Syed Muneeb; Mohammad, Syed Muneeb (International Journal of Contemporary Pediatrics, 2019)
Background: Patent ductus arteriosus (PDA) is a major morbidity encountered in preterm neonates, especially in babies less than 28 weeks gestation or 1000g. It may close spontaneously in preterm neonates; however, failure to close spontaneously in preterm neonates results in significant mortality and morbidity in them. Methods: This prospective study was conducted in a tertiary care hospital in north India over a period of one year. The study cohort consisted of preterm, newborn babies admitted in the hospital with gestational age less than 37weeks and birth weight <2500g. Results: In this study total number of patients admitted during the study were 2930. Out of these preterm low birth weight neonates were 432. Among preterm low birth weight neonates admitted, 132 neonates were excluded as per exclusion criteria. Patent ductus arteriosus was detected in 56 among the 300 neonates giving an overall incidence of patent ductus arteriosus 18.6%, the incidence of patent ductus arteriosus was 56.2% for neonates weighing less than 1000gm, 24.7% for neonates weighing between 1000-1499g, 11.6% for neonates weighing between 1500-1999g and 5.6% for the neonates weighing between 2000-2499g. Conclusions: Thus, incidence of patent ductus arteriosus was inversely proportional to gestational age and birth. Data also suggest that immaturity is the major determinant of the persistent patency of ductus arteriosus.